Influence of Solvothermal Reaction Temperature on Hydroxyapatite Nanowires. Issue 1 (1st January 2023) - Wu, Jinan; Nan, Xiangkai; Qi, Liang; Zhao, Yanwei; Zhang, Haijun; Qi, Mei-li
Abstract: Nowadays, nanomaterials have become the focus of many scientific researchers. As one of the mostly used biomaterials, the special structure and good performance of hydroxyapatite (HA) nanowires is a research hotspot. However, the synthesis of ultralong HA nanowires with highly efficiency and relatively low-cost is still a great challenge. In this work, HA nanowires are successfully synthesized through a simple solvothermal route, with calcium oleate and sodium hexametaphosphate as the calcium and phosphorus source, respectively. Influence of the solvothermal reaction temperature on the HA products are investigated. As the solvothermal temperature increases, the morphology of the HA crystals become nanowires and the length increases. This method is one-step and environmentally friendly without any pollution, since no organic solvent is allowed to be used in the whole experiment. The as-synthesized ultralong HA nanowires have enhanced mechanical properties and can be used in bone tissue engineering, drug delivery, adsorbents, and many other applications.